THE ROLE OF INTERNATIONAL LAW IN PROTECTING HUMAN RIGHTS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This thesis examines the role of international law in protecting human rights in a world marked by complexity and diversity. It traces the foundation of modern human rights law to documents such as the Universal Declaration of Human Rights (UDHR) and explores subsequent treaties and conventions, emphasizing the comprehensive protection they offer across civil, political, economic, social, and cultural dimensions. The thesis highlights the challenges faced in contemporary human rights law, including authoritarian regimes, armed conflicts, and emerging issues like climate change. It discusses a case study of climate refugees to illustrate the gaps in current legal frameworks. Additionally, the thesis proposes avenues for enhancing the role of international law in protecting human rights, such as strengthening compliance mechanisms, promoting accountability, addressing structural injustices, and fostering international cooperation. In conclusion, it underscores the importance of reaffirming commitment to human rights principles and collective action to build a more just and equitable world for all individuals.